The Role Green Economy in Sustainable Development as Long-Term Environmental and Economic Stability: A Literature - Basthiani, Ikrimah Anggita; Pangestuti, Irene Rini Demi (LifeSciFi, 2024)
The purpose of this journal is an attempt to discuss the issues and role of the green economy in the stability of long-term economic and environmental growth. The concept of green economy is one of the global strategies that have links to social, economic and environmental crises. The issue of the green economy concept can achieve the goal of building sustainability where the achievement of sustainable development goals (SDGs) is a major challenge for nations. In particular, SDGs related to environmental sustainability and economic sustainability are most challenging due to high pollution. This research uses the literature review method by looking at and analyzing research data from article and scientific journals that have been reviewed with a series of activities including collecting library data, reading and recording, and managing research materials. The results of this research concept presented in the form of journal articles can be a reference.